Development of a Mobility-Related Quality-of-Life Measure for Individuals with Vision Impairments. (March 2018) - Lethbridge, Emma Marie; Muldoon, Chris
Introduction: Scientifically valid measures of functional vision and quality of life, designed to explore individuals' experiences of vision impairment (that is, blindness and low vision) are widely available; however, there is a paucity of measures specifically considering the quality of life afforded by an individual's mobility. The aim of this research was to develop a mobility-related quality-of-life measure. Methods: An 11-item measure was developed by adapting the Seeing It My Way (Vision Strategy UK, 2011) theoretical framework of outcomes for measuring quality of life when living with vision impairments to explore the effect of mobility. These items are on a seven-point Likert scale from strongly disagree to strongly agree to form the Mobility-Related Quality-of-Life measure (MRQoL). Results: Data from 688 participants revealed that the MRQoL had appropriate reliability, with the items on the scale being highly related and demonstrating sufficient internal consistency. When tested over time without significant intervention, the MRQoL was observed to be stable, with high test-retest reliability. Exploratory factor analysis revealed two distinct sub-factors: factor one, representing a construct containing aspects of independent mobility; and factor two, comprised of the skills and knowledge that enhance mobility. Together, the constructs accounted for 52.2% of the variability within in the data. Discussion: The MRQoL is evidentiarily reliable and has a useful two-factor structure exploring both independent mobility and mobility-enhancing skills and knowledge. Implications for practitioners: The MRQoL is a practical, sensitive, and reliable tool for use in assessing mobility-related quality of life in individuals with vision impairments. The measure is appropriate for use within research or in the field to assess the mobility-related quality of life of individuals or demographics with vision impairments, as well as the success of individual training, group mobility training, or other interventions. The MRQoL measure can be used as a stand-alone tool or alongside other measures.